Review of J. L. Davis and N. Vogeikoff-Brogan (eds), Philhellenism, Philanthropy, or Political Convenience? American Archaeology in Greece; Special issue of Hesperia (2013) - Plantzos, Dimitris (Historein, 2014)
Jack L. Davis and Natalia Vogeikoff-Brogan (eds), Philhellenism, Philanthropy, or Political Convenience? American Archaeology in Greece, Special issue of Hesperia 82/1 (2013). 227 pp.